Pathogenesis and sexual transmission of Spondweni and Zika viruses. - Erin M McDonald; Nisha K Duggal; Aaron C Brault (Public Library of Science (PLoS), 2017)
The Spondweni serogroup of viruses (Flaviviridae, Flavivirus) is comprised of Spondweni virus (SPONV) and Zika virus (ZIKV), which are mosquito-borne viruses capable of eliciting human disease. Numerous cases of ZIKV sexual transmission in humans have been documented following the emergence of the Asian genotype in the Americas. The African ZIKV genotype virus was previously implicated in the first reported case of ZIKV sexual transmission. Reports of SPONV infection in humans have been associated with non-specific febrile illness, but no association with sexual transmission has been reported. In order to assess the relative efficiency of sexual transmission of different ZIKV strains and the potential capacity of SPONV to be sexually transmitted, viral loads in the male reproductive tract and in seminal fluids were assessed in interferon α/β and -γ receptor deficient (AG129) mice. Male mice were inoculated subcutaneously with Asian genotype ZIKV strains PRVABC59 (Puerto Rico, 2015), FSS13025 (Cambodia, 2010), or P6-740 (Malaysia, 1966); African genotype ZIKV strain DakAr41524 (Senegal, 1984); or SPONV strain SAAr94 (South Africa, 1955). Infectious virus was detected in 60-72% of ejaculates collected from AG129 mice inoculated with ZIKV strains. In contrast, only 4% of ejaculates from SPONV-inoculated AG129 males were found to contain infectious virus, despite viral titers in the testes that were comparable to those of ZIKV-inoculated mice. Based on these results, future studies should be undertaken to assess the role of viral genetic determinants and host tropism that dictate the differential sexual transmission potential of ZIKV and SPONV.